Diseño del sistema de gestión de la calidad integrado con el decreto 1443 de 2014, para la empresa Multi-Imágenes Diagnósticas S.A.S. (2017)
This degree project achieves an Integrated Management System design for MULTI IMÁGENES DIAGNOSTICAS S.A.S. company, based on the standars NTC ISO 9001:2015, and Decree 1443 of 2014. The document includes a current diagnose that is the beggining for the Integrated Management System design based on the standars NTC ISO 9001:2015, and Decree 1443 of 2014, allowing the organization to know its current situation and the requirements for the continual improvement, and finally it proposes a Integrated Management System design that help to fulfill the objectives of the organization.